Fabrication of porous micro/nano structured Cr coating with superhydrophobic and ultrahigh adhesion properties by plasma reverse sputtering process. (July 2022) - Ma, Dandan; Lin, Hongchun; Hei, Hongjun; Ma, Yong; Gao, Jie; Zhang, Meng; Yu, Shengwang; Xue, Yanpeng; Tang, Bin
Abstract: In this study, a superhydrophobic Cr porous surface with better abrasive resistance was prepared on Ti6Al4V substrates by double glow plasma surface alloying and the plasma reverse sputtering process. These results showed that the Cr coating with rough and porous micro-nano structures was formed on the surface of Ti6Al4V alloy, which could be attributed to the Kirkendall effect during the process of the plasma reverse sputtering. The role of the reverse sputtering time on the structure and performance of the Cr porous coatings was investigated systematically. The thickness of Cr diffusion layers increased from 13 μm to 28 μm as the reverse sputtering time increased to 45 min. The friction behavior was revealed by wear test, demonstrating prominent improvement of wear resistance. Meanwhile, the as-prepared micro-nano structured Cr coatings exhibited superhydrophobic properties with ultrahigh adhesion. Highlights: A hydrophobic porous Cr surface with good wear resistance was fabricated. The plasma reverse sputtering process induced the formation of porous structures. The sticky superhydrophobic Cr surface can manipulation of water droplets.